Epistemological and Anthropological Thoughts About Neurophilosophy: An Initial Framework - Sonia París Albert; Irene Comins Mingol (Recerca: Revista de Pensament i Anàlisi, 2013)
At the dawn of the twenty-first century, neurophilosophy appears as a branch of neurosciences. The aim of this article is to review critically some of the epistemological and anthropological debates which neurophilosophy is putting on question again. In this sense the philosophical research conducted by the UNESCO Chair of Philosophy for Peace will be used as the main thread of the analysis. To accomplish this critical review, the article has been organized into two parts: the first is of epistemological nature, and the second has an anthropological perspective. This analysis will lead us to question the significance of the contributions of neurophilosophy to a better understanding of the human being.